Uncertainty and risk in the cryptocurrency market - Dora Almeida; Andreia Teixeira Marques Dionísio; Isabel Vieira; Paulo Ferreira (Journal of Risk and Financial Management, 2022)
Cryptocurrency investments are often perceived as uncertain and risky. In this study, we assessed if this is indeed the case, using a sample of seven cryptocurrencies and considered a period that encompassed the first real global shock in the life of these relatively new financial assets, the COVID-19 pandemic. Uncertainty was evaluated using Shannon's symbolic entropy. To measure risk, we use value-at-risk and conditional value-at-risk. The results indicate that, except for Tether, the analyzed cryptocurrencies' returns exhibited similar patterns of uncertainty and risk. Levels of uncertainty were close to the maximum values, but high uncertainty is not always associated with high risk. During the pandemic crisis, uncertainty increased while risk decreased, suggesting that the considered assets may have safe haven properties.
Keywords: 650; risk; uncertainty; cryptocurrencies; symbolic entropy; value-at-risk; conditional value-at-risk